2015
DOI: 10.1016/j.celrep.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cell-Specific Transcriptome Mapping Reveals Regulatory Complexity in the Adult Drosophila Midgut

Abstract: Deciphering contributions of specific cell types to organ function is experimentally challenging. The Drosophila midgut is a dynamic organ with five morphologically and functionally distinct regions (R1-R5), each composed of multipotent intestinal stem cells (ISCs), progenitor enteroblasts (EBs), enteroendocrine cells (EEs), enterocytes (ECs), and visceral muscle (VM). To characterize cellular specialization and regional function in this organ, we generated RNA-sequencing transcriptomes of all five cell types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
268
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(313 citation statements)
references
References 39 publications
31
268
2
Order By: Relevance
“…S6E-F), indicating that adhesion properties are not fundamentally different between cell pair types (at least as far as adherens junctions are concerned). This fits well with the observation that the transcriptional profiles of ISCs and EBs are not particularly enriched with genes involved in cell adhesion (Dutta et al, 2015).…”
Section: −7supporting
confidence: 75%
“…S6E-F), indicating that adhesion properties are not fundamentally different between cell pair types (at least as far as adherens junctions are concerned). This fits well with the observation that the transcriptional profiles of ISCs and EBs are not particularly enriched with genes involved in cell adhesion (Dutta et al, 2015).…”
Section: −7supporting
confidence: 75%
“…Recent gene expression profiling studies indicate that the Drosophila midgut can be functionally divided into several different regions [1, 37, 38]. In particular, the middle region of Drosophila midgut, commonly known as the copper cell region, actually functions as the equivalent of mammalian stomach with its special cell types and physiological features, such as extremely low pH, and cells in this region are maintained by relatively quiescent ISCs known as gastric stem cells [39, 40].…”
Section: N Signaling Regulates the Isc Fate And Lineage Differentiationmentioning
confidence: 99%
“…Using various dpp reporters including enhancer trap line and promoter fusion constructs, it was found that dpp is expressed in trachea cells [60], VMs [41, 56], and ECs [11, 42]. A transcriptome study using sorted midgut cells revealed that dpp is expressed in VMs [37]. On the other hand, RNA in situ hybridization detected dpp expression in ECs [11, 42].…”
Section: Multi-functional Bmp Signaling Regulates Midgut Homeostasis mentioning
confidence: 99%
“…To complete our study, we assessed the functional impacts that the ingestion of low amounts of Btk may have knowing that bacterial intoxication, cell death or the presence of too many immature cells in the gut can affect its digestive functions (Biteau et al, 2008;Buchon et al, 2009b;Chakrabarti et al, 2012;Dutta et al, 2015;Erkosar et al, 2015). Therefore, we monitored several metabolic and enzymatic parameters in the midgut.…”
Section: Physiological Consequencesmentioning
confidence: 99%